PENERAPAN UNDANG-UNDANG NOMOR 13 TAHUN 2006 SEBAGAI BENTUK HUKUM YANG BERSIFAT RESPONSIF (TINJAUAN KASUS PELECAHAN PASIEN OLEH SEORANG PERAWAT) - Rospita A. Siregar (Fakultas Hukum Universitas Kristen Indonesia, 2018)
Abstract The responsive nature of the law according to Philippe Nonet and Philip Selznick aims to achieve competence in order to obtain a sense of justice and meet the expectations of the community, not merely offering procedural justice but substantive justice. The formation of Law number 13 of 2006 concerning Protection of Witnesses and Victims (UUPSK) as a product of regulations that are subordinate to the principles and policies of the government was born as a form of rule of law in society. The results obtained from the testimony of witnesses and victims helped the prosecution of a case. Article 3 states that the protection of witnesses and victims is based on respect for human dignity, security, justice; non-discriminatory and legal certainty. The problem is when witnesses and victims provide information, fear and trauma arise to explain what happened, so that witnesses need protection for themselves and their families. In the case of the abuse of female patients by male nurses in hospitals in East Java, as a result of this unpleasant treatment, the victim’s husband reported to the authorities, the victim’s family demands a form of hope for law enforcement and subsequently obtained justice and legal certainty. The legal process to determine whether a claim is proven in the form of a violation of the law, then there are two elements that must be ful lled namely: the actus reus element or the essential element of crime and mens rea (mental element). Keyword : legal certainty; UUPSK; non-discriminatory; violation of the law.